Do Small, Medium and Micro Enterprises Have the Capacity and will to Employ More People: Solution to Unemployment or Just a Pipe Dream? - Cant, Michael Colin (International Review of Management and Marketing, 2017)
The worldwide economic slump has led to millions of jobs being lost in the formal sector all over the world. This forced many people into business or to seek alternative employment. It has become increasingly clear that the formal sector will rather shed jobs in the foreseeable future than employ people. This has placed renewed focus on small businesses to come to the rescue. More and more governments are relying on these small businesses to create employment opportunities. This has also led to a number of these governments to invest in projects that will generate employment and stimulate economic growth. The obvious choice was to focus on SMMEs. This study evaluated the township SMMEs and their potential to employ more people. The focus was first on the growth or not of these businesses and then on their employment history over the past three years. The findings were encouraging with a large number of SMMEs indicating that their businesses either grew or maintained the status quo while there were positives in the number of people being employed in this sector increasing over the past three years. Keywords: SMME, unemployment, job creation, township, economic growth. JEL Classifications: M0, M2